First enantiospecific synthesis of (+)-beta-herbertenol - Chavan, Subhash P.; Thakkar, M.; Kharul, Rajendra K.; Pathak, A. B.; Bhosekar, Gaurav V.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
The first enantiospecific synthesis of (+)-beta-herbertenol, from naturally occurring R-(+)-citronellal, employing Taber's diazo decomposition protocol as the key step, is described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: citronellal; diazo decomposition; enantiospecific

Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone